Implementation of Child-Friendly Inclusive and Healthy Education Policy for Children with Special Needs - Mahmud, Hirson; Djaafar, Lucyane; Hamim, Udin (Indonesian Journal of Innovation Studies, 2025)
Inclusive education is a vital approach to ensuring equitable access to learning for all students, including children with special needs (ABK). Despite increasing attention to inclusive policies in Indonesia, their implementation at the local level remains varied and often fragmented. Existing studies have not sufficiently explored the operational challenges of the RAIS (Child-Friendly, Inclusive, and Healthy) model, particularly in rural or underserved areas. This study aims to analyze the implementation of the RAIS inclusive education policy for children with special needs at the State Junior High School level in Bulango Ulu District. Using a descriptive qualitative method, data were gathered through interviews with key stakeholders—such as the Education Office, school principals, and supervisors—and supported by secondary documentation. The results reveal suboptimal implementation across planning, execution, and supervision stages. Planning suffers from inadequate technical and financial support; execution is hindered by the lack of trained and accompanying teachers; and supervision remains limited to administrative review. The study offers novelty by highlighting the RAIS model’s current status as a conceptual framework without concrete cross-agency operationalization. The findings imply the need for intersectoral synergy—particularly among the Education, Health, and Child Protection Offices—to ensure RAIS becomes a functional and comprehensive policy for inclusive, equitable education. Highlights: RAIS is still conceptual and lacks operational guidelines. Teacher readiness and support are major implementation gaps. Cross-agency coordination is essential for effective inclusion. Keywords: Inclusive Education, RAIS Model, Children With Special Needs, Policy Implementation, Intersectoral Collaboration